Linking Tools in the Legal Sentence are Applied Examples of Libyan Law Articles - Aisha Hamza Al Fakhri (Journal of Scientific and Human Dimensions, 2026)
Linking devices play a crucial role in legal sentences, connecting clauses and paragraphs, clarifying the relationships between them, and enhancing the clarity and comprehensibility of the legal text. Linking is one of the most important aspects governing the sentence as a linguistic structure. It is achieved through various mechanisms, most notably conjunctions, adverbial connectors, connectives of doubt and reference, tools indicating a departure from reality, explanatory connectors, and other linking devices. A sentence is considered a structural unit that conveys a single semantic meaning, and its independence is a relative concept governed by relationships of connection, linking, and separation within the context. This research will provide a comprehensive overview of linking devices in legal sentences through applied examples from Libyan law